PTG gene deletion causes impaired glycogen synthesis and developmental insulin resistance - Crosson, Sean M. (American Society for Clinical Investigation, 2003)
Protein targeting to glycogen (PTG) is a scaffolding protein that targets protein phosphatase 1α (PP1α) to glycogen, and links it to enzymes involved in glycogen synthesis and degradation. We generated mice that possess a heterozygous deletion of the PTG gene. These mice have reduced glycogen stores in adipose tissue, liver, heart, and skeletal muscle, corresponding with decreased glycogen synthase activity and glycogen synthesis rate. Although young PTG heterozygous mice initially demonstrate normal glucose tolerance, progressive glucose intolerance, hyperinsulinemia, and insulin resistance develop with aging. Insulin resistance in older PTG heterozygous mice correlates with a significant increase in muscle triglyceride content, with a corresponding attenuation of insulin receptor signaling. These data suggest that PTG plays a critical role in glycogen synthesis and is necessary to maintain the appropriate metabolic balance for the partitioning of fuel substrates between glycogen and lipid.